Human geography : landscapes of human activities - Bjelland, Mark D.; Montello, Daniel R., 1959-; Getis, Arthur (New York : McGraw-Hill Education, 2020)
"This thirteen edition of Human Geography retains the organization and structure of its earlier versions. Like them, it seeks to introduce its users to the scope and excitement of geography and its relevance to their daily lives and roles as informed citizens. We recognize that for many students, human geography may be their first or only work in geography and this, their first or only textbook in the discipline. For these students particularly, we seek to convey the richness and breadth of human geography and to give insight into the nature and intellectual challenges of the field of geography itself. Our goals are to be inclusive in content, current in data, and relevant in interpretations. These goals are elusive. Because of the time lapse between world events and the publication of a book, events inevitably outpace analysis. We therefore depend on a continuing partnership with classroom instructors to incorporate and interpret current events and emerging geographic patterns"--
Introduction: some background basis -- Roots and meaning of culture -- Spatial interaction and spatial behavior -- Population: world patterns, regional trends -- Language and religion: mosaics of culture -- Ethnic geography: threads of diversity -- Cultural identities and cultural landscapes: diversity and uniformity -- Economic geography: primary activities -- Economic geography: manufacturing and services -- Economic development and change -- Urban systems and urban structures -- The political ordering of space -- Human impacts on the environment.
Includes bibliographical references and index.
Keywords: Human geography